First Report of Troglotrema acutum Trematoda Parasitizing a European Polecat (Mustela putorius) in Bulgaria - Mike Heddergott (Parasitologia)
The finding also represents the first detection of this trematode on the Balkan Peninsula. The study was conducted between 2014 and 2023. Nineteen road-killed polecats, mainly from southern Bulgaria, were examined. A four-year-old male polecat road-killed near Chepelare, a town in the Somlyan Province in the Rhodope Mountains, was infested with six adult Troglotrema acutum within its frontal sinus. The skull exhibited only weakly developed lesions. The prevalence of 5.26% observed in this sample was lower than values reported from other European countries. This finding extends the known southeastern distribution range of T. acutum by over 700 km.